High-affinity glucose transport in Saccharomyces cerevisiae is under general glucose repression control. - Bisson, L F (1988)
Saccharomyces cerevisiae mutants defective in growth on low glucose concentration (lgn mutants) were isolated and screened for abnormal glucose transport. Nine complementation groups were identified, falling into two broad groups: those unable to significantly derepress high-affinity (low-Km) glucose uptake (lgn1, lgn4, lgn5, lgn7, and lgn8), and those with elevated repressed levels of high-affinity uptake that either derepress to normal or near normal levels of high-affinity uptake with loss of low-affinity transport (lgn2 and lgn3) or derepress only slightly, appearing to have an intermediate yet constitutive level of high-affinity transport (lgn6 and lgn9). Further analysis of the lgn mutations revealed pleiotropic phenotypes most consistent with the true defect being in regulation or expression of glucose repression and derepression. The kinetics of glucose uptake in strains carrying known mutations preventing derepression of glucose-repressible functions (snf1, snf2, snf4, and snf6) demonstrated that three of these mutations (snf1, snf4, and snf6) were similarly defective in derepression of high-affinity glucose uptake. The snf2 and snf5 mutations had no apparent effect on glucose uptake. Two mutations resulting in constitutive expression of glucose-repressible functions, cid1 and reg1, resulted in constitutive expression of high-affinity glucose uptake. These data support the conclusion that high-affinity glucose uptake in Saccharomyces cerevisiae is under general glucose repression control. The implications of other properties of these mutants are discussed.